Avaliação da atividade antibacteriana, citotóxica e nuclease química de complexos triazenidos de platina (II) - Garzon, Litiérri Razia (2015)
Despite the large number of antimicrobials and anti-tumor drugs, therapeutic arsenal is limited due to the emergence of bacterial resistance mechanisms and refractoriness, besides the toxicity of certain drugs. This has contributed to advances in scientific research, especially those aimed at obtaining new active agents against infectious diseases and cancer, with innovative and less toxicity mechanisms. From this perspective, due to the great versatility and diverse pharmacological properties demonstrated by triazenes (TZCs) This study aimed to evaluate in vitro biological activity of two compounds unpublished TZCs complexed with platinum (II): {trans [1- (2-bromophenyl ) -3- (2-nitrophenyl) triazenido) bis (pyridine) (chloro) platinum (II)} (C1) and cis- {[1- (2-nitrophenyl) -3- (2-bromofenil) triazenido)] (ditrifenilfosfina ) (chloro) platinum (II)} (C2). The antibacterial activity was performed by the conventional method of broth microdilution, by evaluating the minimum inhibitory concentration (MIC) against the bacterial strains benchmark American Type Culture Collection (ATCC) and clinical isolates with multiple resistance to drugs (RMD). Cytotoxicity was assessed by colorimetric assay based on reduction of 3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyltetrazolium bromide (MTT) compared to the bone marrow cells from patients diagnosed with leukemia treated at the University Hospital of Santa Maria. The chemical nuclease activity was verified by electrophoresis in agarose gel. According to the results showed that both compounds have antibacterial activity TZCs. The C1 complex showed activity against E. faecalis 51299, 15305 S. saprophyticus, E. faecalis 29212, S. aureus ATCC 25923 and S. aureus ATCC 29213. The C2 complex was able to inhibit growth of a bacterium RMD S. epidermidis 27. The studied complexes showed narrow spectrum of activity being active only against Gram positive bacteria. In addition, C1 promoted high percentage of cell death in the face of patient cells with Chronic Myeloid Leukemia (LMC) of 50.23% 75.59% will. With respect to nuclease activity, in investigated conditions, the compounds were not able to cleave the plasmid DNA. This study reflects the broad antimicrobial and cytotoxic activity of TZCs compounds.